Оцінювання ефективності медичних лабораторних систем - Веретельніков, Д. М. (ХНУРЕ, 2023)
The field of medicine is quite developed nowadays: new high-tech methods of treatment are being researched and multifunctional solutions are being created to improve information systems, in particular for medical laboratories. This work presents the classification of medical laboratories depending on their specialization. Various laboratory information systems (LIS) were divided into types with examples of existing products. The methods of evaluating the effectiveness of laboratory information systems were determined and ordered according to the expediency of use.